Factors Impeding Mobile Money Expansion in Zambia - Natalie Chipa; Bupe Getrude Mwanza (International Journal of Engineering and Management Research, 2021)
The majority of the world population is not covered by the mainstream financial sector. As such, mobile money services are seen as a cost effective and efficient way of increasing financial inclusion. However, there remains some factors that impede the development of mobile money services. Therefore, this study sought to analyse these factors with a view to identifying strategies that can be used to accelerate the development of mobile money services.